The new imagine attention model and its effect on the customer satisfaction of the Interbank Bank of the Comas store 138, year 2015 - 2017 - Cauti Escobar, Luis Enrique (2020)
The present research is focused on being able to demonstrate that the new Imagine service model has an effect on the satisfaction of the Interbank Bank customers of the Comas 138 store, in order to verify the acceptance of this new service model. In this sense, the research is of an applicative type since all its aspects are theorized, although its scope is practical, also the design is correlational since its purpose is to describe the relationship of the variables and examine their impact. The data was obtained through surveys carried out on a sample of 277 clients. Therefore, the measurement and analysis of the reliability of the correlation coefficient was carried out, as well as the Cronbach’s Alpha score, obtaining 0.97 as a result, which is why it is determined that there is a very good correlation between the new Imagine care model and its effect on the satisfaction of the Interbank Bank customers of the Comas 138 store. In summary, it is true to say that the new service model Imagine if it has an effect on the satisfaction of the Interbank bank customers of the Comas 138 store.